Premedication and management of concomitant therapy. Issue 8 (August 2019) - Scott, Ashley; Timms, Gemma
Abstract: The management of a patient's co-existing illnesses, including decisions about their normal medication is an important part of their perioperative care. Adequate pre-assessment, preparation and liaison with other healthcare professionals is essential to decrease patient morbidity and mortality and prevent unnecessary surgical delay or suboptimal management. A full medication history including prescribed, over the counter and complementary medications is required, along with decisions regarding which medications should be omitted or have dose alterations. Medications may need to be prescribed in addition to the patient's normal medications, for example, thromboembolic prophylaxis. This article summarizes current recommendations with regard to premedication and concomitant medication.